Interleukin-10 responses to therapeutic vaccination during highly active antiretroviral therapy and after analytical therapy interruption. - Yang, H; Guimarães-Walker, A; Hibbs, S; Dong, T; Stacey, A; Borrow, P; Hanke, T; Davenport, M; McMichael, A; Dorrell, L (2009)
We investigated whether therapeutic vaccination in highly active antiretroviral therapy (HAART)-treated patients with a modified vaccinia virus Ankara-vectored HIV-1 vaccine, with or without therapy interruption, induced the production of interleukin (IL)-10. Plasma IL-10 levels were not significantly increased postvaccination, but increased in parallel with viraemia in patients who interrupted therapy. Surprisingly, IL-10 blockade augmented HIV-specific T cell proliferative responses in HAART-suppressed patients but had no effect once virological control was lost. Modulation of IL-10 might enhance vaccine-induced immune responses.